Enhanced photovoltaic performance using reduced graphene oxide assisted by triple-tail surfactant as an efficient and low-cost counter electrode for dye-sensitized solar cells - A.B., Suriania; M.D., Nurhafizaha; A., Mohamed; M.H., Mamat; M.F., Malek; M.K., Ahmad; A., Pandikumar; N.M., Huang (Elsevier Science Ltd, 2017)
In this work, 4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-silphonate (TC14) surfactant assisted reduced graphene oxide (rGO) was used as a counter electrode (CE) in dye-sensitized solar cell (DSSC). Field emission scanning electron microscopy and high-resolution transmission electron microscopy observations revealed that the TC14-rGO film was well dispersed on fluorine-doped tin oxide surface. The TC14-rGO modified CE based DSSC showed a power conversion efficiency of 0.828%, a short current density (JSC) of 2.72 mA cm−2, an open circuit voltage (VOC) of 0.65 V, and a fill factor (FF) of 41.9 which were higher than those CE fabricated from commercially available SDS surfactant assisted rGO. Results revealed that TC14-rGO is a potential CE material to construct efficient DSSC for future solar cell applications.